2013
DOI: 10.2119/molmed.2012.00260
|View full text |Cite
|
Sign up to set email alerts
|

MFG-E8 and HMGB1 Are Involved in the Mechanism Underlying Alcohol-Induced Impairment of Macrophage Efferocytosis

Abstract: Efferocytosis is a unique phagocytic process for macrophages to remove apoptotic cells in inflammatory loci. This event is maintained by milk fat globule-EGF factor 8 (MFG-E8), but attenuated by high mobility group box 1 (HMGB1). Alcohol abuse causes injury and inflammation in multiple tissues. It alters efferocytosis, but precise molecular mechanisms for this effect remain largely unknown. Here, we showed that acute exposure of macrophages to alcohol (25 mmol/L) inhibited MFG-E8 gene expression and impaired e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 49 publications
(84 reference statements)
3
40
0
Order By: Relevance
“…Efferocytosis dysfunction may lead to excessive accumulation of late apoptotic and/or secondary necrotic cells and subsequent inflammatory response. Compared with milk fat globule-EGF factor 8 (MFG-E8) (Miksa et al, 2009; Wang et al, 2013k), HMGB1 is a negative regulator of efferocytosis by its C-terminal acidic tail (Banerjee et al, 2010) and poly(ADP-ribosyl)ation (Davis et al, 2012b). Extracellular HMGB1 inhibits efferocytosis by binding phosphatidylserine or α ν β 3 integrin in apoptotic neutrophils or phagocytic macrophages, respectively (Friggeri et al, 2010; Liu et al, 2008a).…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…Efferocytosis dysfunction may lead to excessive accumulation of late apoptotic and/or secondary necrotic cells and subsequent inflammatory response. Compared with milk fat globule-EGF factor 8 (MFG-E8) (Miksa et al, 2009; Wang et al, 2013k), HMGB1 is a negative regulator of efferocytosis by its C-terminal acidic tail (Banerjee et al, 2010) and poly(ADP-ribosyl)ation (Davis et al, 2012b). Extracellular HMGB1 inhibits efferocytosis by binding phosphatidylserine or α ν β 3 integrin in apoptotic neutrophils or phagocytic macrophages, respectively (Friggeri et al, 2010; Liu et al, 2008a).…”
Section: Hmgb1 Functionmentioning
confidence: 99%
“…Twenty-four hours after transfection, cells were treated with LPS (100 ng/ml) or vehicle (i.e. control) for 24 h and luciferase assay was performed with a standard protocol as previously described [Wang et al, 2013]. We found that the relative luciferase activity was reduced by 38.7 ± 1.1 % in pGL3-444/+146-transfected cells and 23.4 ± 0.47% in pGL3-94/+146-transfected cells 24 h after LPS treatment ( P <0.05) compared to control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Murine peritoneal macrophages were isolated using a standard protocol in our lab [Bu et al, 2006; Wang et al, 2013]. The procedure was conducted according to the Materials and Methods approved by the Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations